Rheological and Microstructure Characterization of Composite Dough with Wheat and Mesquite (Prosopis spp) Flours - Bigne, Facundo (2016)
Rheological behavior and microstructural characteristics of composite dough with wheat and mesquite flours (from Prosopis alba) were analyzed by response surface methodology. A central composite design was applied varying proportions of water (50 to 80 g each 100 g wheat flour) and mesquite flour (0 to 70 each 100 g wheat flour). Texture profile analysis showed that increasing the amount of mesquite flour and decreasing the amount of water led to less cohesive and more resilient doughs. Stress relaxation curves were fitted with a Maxwell model and relaxation times were obtained. These parameters resulted higher for those formulations low in mesquite content and high water levels. Composite dough showed a typical viscoelastic behavior with higher elastic moduli (G) when mesquite flour ratio in the mixture was increased. 1H-RMN T2 relaxation assays revealed higher mobility in samples with high amounts of water and minimum level of mesquite. A farinograph was adequate to obtain optimum water amounts and showed that addition of mesquite led to less stable dough respect to control wheat dough. By using confocal laser scanning microscopy with fluorescent probes rhodamine B and fluoresceine isothiocyanate, a poor gluten network development or protein aggregation was observed when water contents were far from optimum.